2015
DOI: 10.1002/iub.1460
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotyping in Egyptian diabetic nephropathy patients

Abstract: Research for the causes of diabetic nephropathy has focused on the study of the affected familial disease clusters. The polymorphism in apolipoprotein E (ApoE) has been linked to the development of diabetic nephropathy (DN) in association with hyperlipidemia. The aim of this study was to evaluate the association of this condition with ApoE gene polymorphism connected with DN in diabetic Egyptian subjects. One hundred and thirty-five patients were enrolled in the study, they were divided into three groups: 45 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The inconsistency may result from the difference of included population, sample size, and genotyping methods. Moreover, 18 new papers (CHEN 2006;TANG et al 2007;ERDOGAN et al 2009;AL-MAJED et al 2011;CHAUDHARY et al 2012;MUSTAPIC et al 2012;GE et al 2013;RONG et al 2013;SUN et al 2013a;XIONG et al 2013;ALHARBI et al 2014;LIU 2014;WANG et al 2014;ATTA et al 2016;LIU et al 2016;LUO et al 2016;MEHMET et al 2016;LIANG et al 2017) have been published since the publication of latest meta-analysis of the association between ApoE gene polymorphism and T2DM in 2014 (YIN et al 2014). Therefore, we enrolled these new published articles, and performed a further meta-analysis to investigate whether ApoE polymorphism is associated with the increased risk of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…The inconsistency may result from the difference of included population, sample size, and genotyping methods. Moreover, 18 new papers (CHEN 2006;TANG et al 2007;ERDOGAN et al 2009;AL-MAJED et al 2011;CHAUDHARY et al 2012;MUSTAPIC et al 2012;GE et al 2013;RONG et al 2013;SUN et al 2013a;XIONG et al 2013;ALHARBI et al 2014;LIU 2014;WANG et al 2014;ATTA et al 2016;LIU et al 2016;LUO et al 2016;MEHMET et al 2016;LIANG et al 2017) have been published since the publication of latest meta-analysis of the association between ApoE gene polymorphism and T2DM in 2014 (YIN et al 2014). Therefore, we enrolled these new published articles, and performed a further meta-analysis to investigate whether ApoE polymorphism is associated with the increased risk of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiology studies showed that the occurrence of DN is affected by the combined actions of multiple factors [5,6]. Among these factors, genetic factors play a crucial role in DN onset, and many genes are found [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed that E2/E3 genotype and ε2 allele were independent risk factors for DN, while the E3/E3 genotype and ε3 allele were protective factors, consistent with the previous research. 38,[52][53][54] APOE gene polymorphism significantly influenced serum lipid profiles in DN patients. APOE is a crucial plasma protein primarily synthesized, secreted, and metabolized by the liver, and it was synthesized in many other organs, including adrenal gland and kidney.…”
Section: Discussionmentioning
confidence: 99%